(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The journey begins with an exploration of the fundamental principles of energy-efficient building design, encompassing architectural considerations, engineering solutions, food science insights, and environmental factors. Within this framework, we examine the pivotal roles played by building layout, envelope design, natural lighting, HVAC systems, lighting systems, and renewable energy integration. Additionally, we delve into the nexus between food science and energy conservation, shedding light on process optimization, packaging, storage impacts, and waste reduction strategies. The landscape of environmental and regulatory factors is also scrutinized, emphasizing compliance with energy standards, sustainability certifications, and government incentives as drivers for energy-efficient practices.